Pengaruh Sales Growth dan Struktur Modal terhadap Harga Saham Dengan Ukuran Perusahaan Sebagai Variabel Moderating (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclical yang Terdaftar di BEI Tahun 2017-2022) - Febrina, Andani Bias; Margie, Lyandra Aisyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of Sales Growth and Capital Structure on Share Prices with Firm Size as a Moderating Variable in the Consumer Non-Cyclical sector listed on the Indonesia Stock Exchange for the 2017-2022 period. Based on the purposive sampling method, the population used in this research was 112 companies with a selected sample of 34 companies. Statistical testing uses Econometric Views 12. The results of this study show that (1) Partial sales growth does not have a significant effect on stock prices, (2) Partial capital structure has a significant effect on stock prices, (3) Partial sales growth and capital structure simultaneously has a significant effect on the Stock Price variable, (4) Firm Size is not able to moderate the influence of Sales Growth on Stock Prices, (5) Firm Size is able to moderate the relationship between the Capital Structure variable and Stock Prices.